1999
DOI: 10.1016/s0008-6363(99)00104-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic regulation of arterial blood pressure in ANP transgenic and knockout mice: Role of cardiovascular sympathetic tone

Abstract: The present study shows that differences in endogenous ANP activity in mice, resulting in chronic alterations in ABP are accompanied by directional changes in underlying cardiovascular sympathetic tone, and suggests that the chronic vasodilator effect of ANP is, at least partially, dependent on attenuation of vascular sympathetic tone, possibly at a prejunctional site(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
1
47
0
1
Order By: Relevance
“…In both adrenal gland and SNS nerve terminals, NP reduce CA production via a cGMP-dependent activation of tyrosine hydroxylase, the rate-limiting enzyme in CA synthesis (Holtz et al, 1987). This effect is corroborated by the high circulating CA levels found in genetically modified mice with ANP gene disruption (Melo et al, 1999). On the other hand, the effects of adrenergic stimulation on mammalian cardiac NP release are still in part unknown because of confusing results mainly derived from clinical studies carried out in the presence of different pathological conditions and/or therapies.…”
Section: Np Ca and The Stressed Heartmentioning
confidence: 76%
“…In both adrenal gland and SNS nerve terminals, NP reduce CA production via a cGMP-dependent activation of tyrosine hydroxylase, the rate-limiting enzyme in CA synthesis (Holtz et al, 1987). This effect is corroborated by the high circulating CA levels found in genetically modified mice with ANP gene disruption (Melo et al, 1999). On the other hand, the effects of adrenergic stimulation on mammalian cardiac NP release are still in part unknown because of confusing results mainly derived from clinical studies carried out in the presence of different pathological conditions and/or therapies.…”
Section: Np Ca and The Stressed Heartmentioning
confidence: 76%
“…Vasodilatation 68 Modulation of endothelial permeability 69 Central Nervous System Effects Modulation of sympathetic activity 70,71 Inhibition of arginine vasopressin secretion 47,72 Diminished salt appetite and water drinking 47,60 Effects on blood pressure/volume-regulating regions in the brain 47,60 than do ANP-deficient mice. Whereas BNP-deficient mice do not have hypertension or cardiac hypertrophy, they are susceptible to cardiac fibrosis.…”
Section: Vascular Effectsmentioning
confidence: 99%
“…47,60 -72 In particular, the renal [63][64][65][66] and sympatholytic actions of ANP 70,71 probably have a major role in the hypotensive actions of the peptide. In contrast, the relevance of the direct vasodilating ANP effect is controversial, because very variable GC-A levels are expressed in different vascular beds.…”
Section: Endocrine Actions Of the Anp/gc-a System Cooperate In Acute mentioning
confidence: 99%
“…The diuretic, natriuretic and vasodilator actions of natriuretic peptides are mediated by cell membrane natriuretic peptide receptor A (NPR-A) and NPR-B, through activation of guanylyl cyclase/cGMP, and NPR-C (clearance receptor), through inhibition of adenylyl cyclase/cAMP. The important role of ANP on chronic blood pressure regulation has been shown in a transgenic mouse model overexpressing ANP (26,27), where elevated plasma ANP was associated with significant blood pressure reduction, whereas NPR-A knockout mice are hypertensive. The knockout studies revealed that the chronic hypotensive effect of ANP is mediated by attenuation of cardiovascular sympathetic tone (27).…”
Section: Imidazoline and Natriuretic Peptidesmentioning
confidence: 99%
“…The important role of ANP on chronic blood pressure regulation has been shown in a transgenic mouse model overexpressing ANP (26,27), where elevated plasma ANP was associated with significant blood pressure reduction, whereas NPR-A knockout mice are hypertensive. The knockout studies revealed that the chronic hypotensive effect of ANP is mediated by attenuation of cardiovascular sympathetic tone (27). Independent of their role in blood pressure control, natriuretic peptides have antiinflammatory effects, and exert direct antihypertrophic and anti-fibrotic actions on the heart.…”
Section: Imidazoline and Natriuretic Peptidesmentioning
confidence: 99%